Pulmonary Fibrosis and Hypereosinophilia in TLR9-/- Mice Infected by Cryptococcus gattii - Elias Barbosa da Silva-Junior; Israel Diniz-Lima; Amanda Couto Silva; Joyce Cristina Guimarães-de-Oliveira; Alexandre Morrot; Leonardo Freire-de-Lima; Leonardo Marques da Fonseca; Lycia de Brito-Gitirana; Debora Decote-Ricardo; Herbert Leonel de Matos Guedes; Celio Geraldo Freire-de-Lima (Pathogens, 2022)
Cryptococcus gattii is a worldwide-distributed basidiomycetous yeast that can infect immunocompetent hosts. However, little is known about the mechanisms involved in the disease. The innate immune response is essential to the control of infections by microorganisms. Toll-like receptor 9 (TLR9) is an innate immune receptor, classically described as a non-methylated DNA recognizer and associated with bacteria, protozoa and opportunistic mycosis infection models. Previously, our group showed that TLR9-/- mice were more susceptible to C. gattii after 21 days of infection. However, some questions about the innate immunity involving TLR9 response against C. gattii remain unknown. In order to investigate the systemic cryptococcal infection, we evaluated C57BL/6 mice and C57BL/6 TLR9-/- after intratracheal infection with 104C. gattii yeasts for 21 days. Our data evidenced that TLR9-/- was more susceptible to C. gattii. TLR9-/- mice had hypereosinophilia in pulmonary mixed cellular infiltrate, severe bronchiolitis and vasculitis and type 2 alveolar cell hyperplasia. In addition, TLR9-/- mice developed severe pulmonary fibrosis and areas with strongly birefringent fibers. Together, our results corroborate the hypothesis that TLR9 is important to support the Th1/Th17 response against C. gattii infection in the murine experimental model.